2020
DOI: 10.1111/ctr.14004
|View full text |Cite
|
Sign up to set email alerts
|

Does graft hemodynamics affect the risk of hepatocellular carcinoma recurrence after liver transplantation?

Abstract: Although experimental studies have reported that hepatic ischemia‐reperfusion injury promotes tumor growth and metastases, the impact of graft hemodynamics on the recurrence of hepatocellular carcinoma (HCC) after liver transplantation (LT) is unclear. To investigate the association between graft hemodynamics and HCC recurrence after LT, we conducted a retrospective analysis of 279 patients who underwent LT for HCC. Graft hemodynamics including portal vein flow (PVF), hepatic artery flow (HAF), and total hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Regarding the marginal graft, HOPE treatment markedly ameliorated IRI with decreased oxidative stress, less nuclear injury, reduced Kupffer and endothelial cell activation and less fibrosis within one week post transplantation [ 126 ]. In addition to the studies in animal models, a recent clinical retrospective study demonstrated that low total hepatic flow was significantly associated with tumor recurrence, indicating that graft hemodynamics affect HCC recurrence after liver transplantation [ 127 ]. Due to the mechanistic link between IRI and HCC recurrence, dynamic liver preservation approaches may serve as promising strategies to decrease HCC recurrence.…”
Section: Therapeutic Strategies To Reduce Both Short- and Long-term Impacts Of Inflammation In Hepatic Irimentioning
confidence: 99%
“…Regarding the marginal graft, HOPE treatment markedly ameliorated IRI with decreased oxidative stress, less nuclear injury, reduced Kupffer and endothelial cell activation and less fibrosis within one week post transplantation [ 126 ]. In addition to the studies in animal models, a recent clinical retrospective study demonstrated that low total hepatic flow was significantly associated with tumor recurrence, indicating that graft hemodynamics affect HCC recurrence after liver transplantation [ 127 ]. Due to the mechanistic link between IRI and HCC recurrence, dynamic liver preservation approaches may serve as promising strategies to decrease HCC recurrence.…”
Section: Therapeutic Strategies To Reduce Both Short- and Long-term Impacts Of Inflammation In Hepatic Irimentioning
confidence: 99%